LEARNING PROPER NAMES - Koziyeva Iqbol Komiljonovna (American Journals Publishing, 2025)
This article examines the position of proper names in the language and their difference from common names since ancient times. Attempts at theoretically grounded problems and their solutions are considered.
Keywords: Proper name, calculus, common names, nickname, term.